1994
DOI: 10.1007/bf00227513
|View full text |Cite
|
Sign up to set email alerts
|

Ear and eye representation in the frontal cortex, area 8b, of the macaque monkey: an electrophysiological study

Abstract: We evoked both ear and eye movements in area 8b, the rostral area of frontal cortex, in two monkeys. In some sites it was possible to evoke only ear movements or only eye movements; in other locations we evoked both ear and eye movements by varying the intensity of electrical stimulation. The electrically evoked ear movements were forward, or backward, or oblique (upward-forward; upward-backward). In two penetrations the ear movements were bilateral, in the other penetrations they were contralateral. Ipsilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 19 publications
5
34
1
Order By: Relevance
“…The small region with a high concentration of saccaderelated neurons described by these authors is surrounded by a much larger area also containing saccade-related neurons, albeit less frequently, which encompasses the supplementary motor area (SMA), the pre-SMA, and areas of the exposed surface lateral, caudal, and rostral to the SEF (Fujii et al, 1995). Consistent with this, the fact that saccades are evoked in response to electrical stimulation of areas 6 (Shook et al, 1988) and 8B (Bon and Lucchetti, 1994) and the fact that saccade-related cells are encountered in areas 8B (Bon and Lucchetti, 1994) and 9 (Joseph and Barone, 1987), we found additional transneuronally labeled neurons in areas 6, 8B, 9, and corresponding mesial cortical regions.…”
Section: The Dorsomedial Frontal Cortexsupporting
confidence: 53%
“…The small region with a high concentration of saccaderelated neurons described by these authors is surrounded by a much larger area also containing saccade-related neurons, albeit less frequently, which encompasses the supplementary motor area (SMA), the pre-SMA, and areas of the exposed surface lateral, caudal, and rostral to the SEF (Fujii et al, 1995). Consistent with this, the fact that saccades are evoked in response to electrical stimulation of areas 6 (Shook et al, 1988) and 8B (Bon and Lucchetti, 1994) and the fact that saccade-related cells are encountered in areas 8B (Bon and Lucchetti, 1994) and 9 (Joseph and Barone, 1987), we found additional transneuronally labeled neurons in areas 6, 8B, 9, and corresponding mesial cortical regions.…”
Section: The Dorsomedial Frontal Cortexsupporting
confidence: 53%
“…The rostral territory, area OMD (Stepniewska et al, 1993a), is architectonically dysgranular, and resembles the cortex denoted as area 8b in other primates (Walker, 1940; see also di Pelligrino and Wise, 1991;Preuss and Goldman-Rakic, 1991;Bon and Lucchetti, 1994). OMD may be less responsive to stimulation than PMD or SMAd, as evidenced by the presence of many unresponsive points in OMD or points that required very strong currents to elicit movements.…”
Section: Organization Of Premotor Cortex In Owl Monkeysmentioning
confidence: 96%
“…Nevertheless, there is some evidence that both 8b and PMD are involved in eye-movement control in macaques as well. Bon and Lucchetti (1994) have reported eliciting eye and ear movements from area 8b in macaques. Mitz and Godschalk (1989) also elicited eye movements in macaques from sites located rostral to the superior tip of the arcuate sulcus, a region that probably corresponds to area 8b.…”
Section: Organization Of Premotor Cortex In Macaquesmentioning
confidence: 97%
“…For example, Petrides proposed that the dorsomedial PFC plays important roles in monitoring multiple events and self-ordering actions (13), although his later study suggested that the dlPFC is also involved in this process (14). Bon and Lucchetti reported that electrical stimulation in area 8b evoked ear or eye movements, and neurons in this region showed activity modulation related to these types of movements (15,16). Human brain-imaging studies identified active areas including the mPFC that were related to the selection of actions and conflict monitoring (17) or to the generation and adjustment of action plans (18).…”
mentioning
confidence: 99%